2012
DOI: 10.1002/14651858.cd003857.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of fibroids for subfertility

Abstract: There is currently insufficient evidence from randomised controlled trials to evaluate the role of myomectomy to improve fertility. Regarding the surgical approach to myomectomy, current evidence from two randomised controlled trials suggests there is no significant difference between the laparoscopic and open approach regarding fertility performance. This evidence needs to be viewed with caution due to the small number of studies. Finally, there is currently no evidence from randomised controlled trials regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 35 publications
2
64
0
9
Order By: Relevance
“…A systematic review of two randomized control trials evaluating a total of 293 patients allocated to either open or laparoscopic myomectomy reported no significant effect on the live birth rate (OR 0.80, 95% CI 0.42 to 1.50), clinical pregnancy rate (OR 0.96, 95% CI 0.52 to 1.78), ongoing pregnancy rate (OR 1.61, 95% CI 0.26 to 10.04), miscarriage rate (OR 1.31, 95% CI 0.40 to 4.27), or preterm labor rate (OR 0.68, 95% CI 0.11 to 4.43). 30 Recurrence of fibroids post-myomectomy has been associated with adverse obstetrical outcome. Sudik et al performed a comparative, retrospective non-randomized clinical study including 67 patients undergoing myomectomy for fertility and reported a higher rate of preterm delivery (38.5% vs. 0%) and cesarean section (84.6% vs. 38.8%) in patients with recurrent fibroids (N=31) compared with the recurrence-free control group (N=36).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of two randomized control trials evaluating a total of 293 patients allocated to either open or laparoscopic myomectomy reported no significant effect on the live birth rate (OR 0.80, 95% CI 0.42 to 1.50), clinical pregnancy rate (OR 0.96, 95% CI 0.52 to 1.78), ongoing pregnancy rate (OR 1.61, 95% CI 0.26 to 10.04), miscarriage rate (OR 1.31, 95% CI 0.40 to 4.27), or preterm labor rate (OR 0.68, 95% CI 0.11 to 4.43). 30 Recurrence of fibroids post-myomectomy has been associated with adverse obstetrical outcome. Sudik et al performed a comparative, retrospective non-randomized clinical study including 67 patients undergoing myomectomy for fertility and reported a higher rate of preterm delivery (38.5% vs. 0%) and cesarean section (84.6% vs. 38.8%) in patients with recurrent fibroids (N=31) compared with the recurrence-free control group (N=36).…”
Section: Discussionmentioning
confidence: 99%
“…This patient group has a rate of abnormal uterine bleeding of 70-80% and it constitutes an indication for hysteroscopic myomectomy [3,4,7,12]. Since Neuwith and Amin [5] technological hardware has developed making hysteroscopic resection a minimally invasive and standard treatment modality for submucosal myoma.…”
Section: Discussionmentioning
confidence: 99%
“…Since Neuwith and Amin [5] technological hardware has developed making hysteroscopic resection a minimally invasive and standard treatment modality for submucosal myoma. Especially with fertility and protecting the organ the current ideal in choosing a surgical treatment, this brings hysteroscopic resection to the fore compared with other choices for submucosal myoma treatment [9,12]. There is no meta-analysis in the literature of HRSM done due to AUB.…”
Section: Discussionmentioning
confidence: 99%
“…Metaanalízis során a myomák fertilitásra gyakorolt hatásáról egyértelmű, erős evidenciákat azonban nem sikerült felállítani [18].…”
Section: öSszefoglaló Közleményunclassified